Predictors of Cognitive Decline in the Early Stages of Parkinson's Disease: A Brief Cognitive Assessment Longitudinal Study - Paulo Bugalho; Miguel Viana-Baptista (Parkinson's Disease)
Our objectives were to perform a longitudinal assessment of mental status in early stage Parkinson’s disease (PD) patients, with brief neuropsychological tests, in order to find predictive factors for cognitive decline. Sixty-one, early stage, and nondemented patients were assessed twice, over a 2-year interval, with a global cognitive test (mini-mental state examination (MMSE)) and a frontal function test (frontal assessment battery (FAB)) and motor function scales. Dementia and hallucinations were diagnosed according to the DSM-IV criteria. Cognitive function scores did not decrease significantly, except for FAB lexical fluency score. Four patients presented with dementia at followup. The MMSE score below cut-off, worse gait dysfunction, the nontremor motor subtype, and hallucinations were significantly related to dementia. Rigidity and speech dysfunction were related to dementia and a decrease in FAB scores. We can conclude that decline in the MMSE and FAB scores is small and heterogeneous in the early stages of PD. Scores below cut-off in the MMSE could be helpful to predict dementia. Nontremor motor deficits could be predictive factors for frontal cognitive decline and dementia.